Application Of Mathematical Literacy In Mathematics Learning For Elementary School - Fadhilah Fitri; Dina Fitria; Fridgo Tasman; Defri Ahmad; Suherman Suherman (Fakultas MIPA Universitas Negeri Padang, 2019)
Mathematical literacy requires individuals to solve a problem and also apply mathematics in everyday problems, which results in the ability to interpret solutions to those problems. In PISA it is known that Indonesia's mathematics literacy score is among the lowest, as well as in Guguk District Lima Puluh Kota Regency. One way to overcome this is to start introducing literacy to students early on. The introduction of literacy must be instilled in students since they are still in elementary school. Based on this, a training program and workshop was held regarding the application of mathematical literacy in mathematics learning in elementary schools in Guguak District with elementary school mathematics teacher partners who are members of the KKG SD Gugus III Kecamatan Guguak Kabupaten Lima Puluh Kota.